Towards high milling accuracy of turbine blades: A review. (1st May 2022) - Yan, Boling; Hao, Yanpeng; Zhu, Lida; Liu, Changfu
Graphical abstract: Highlights: The deformation and machining errors in blade milling are firstly discussed, including the interaction of cutting force and deformation, error detection and compensation. The issues on vibration and surface quality are investigated to study the prediction, monitoring and control of vibration, along with discussions on the impact of vibration on surface roughness. Finally, crucial conclusions on current research status and the future trends are summarized and prospected. Abstract: Turbine blades are widely used in aviation industries for its aero-dynamic performance. However, as a kind of thin-walled parts with complex surfaces, to machine blades with high quality and efficiency remains a challenging task for the time being. This paper provides a review on recent study progress in milling of blades. To begin with, computer aided design/machining (CAD/CAM) techniques of blades are discussed. Subsequently, a detailed review on cutting force, machining error and surface quality of blade milling are presented. Both discussed issues are presented in-depth in a sequence of theory and application. Finally, crucial conclusions on current research status and the future trends are summarized and prospected.